Pelatihan Teknologi Sistem Informasi bagi Nelayan pada Masa Covid-19 di Era Digital - Ismail Ismail; Endang Gunaisah; Muhfizar; M. Ali Ulat; Hendra Poltak (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2021)
Information system technology is changing so fast connecting a world without limits. The ability to access unlimited information resources can be a medium to improve the welfare and independence of all groups of people, including the fishermen group. However, the low level of human resources is an inhibiting factor in understanding information technology so there are limitations in accessing new knowledge to improve their welfare.Community service provides solutions for partners through training delivered through conventional and online and mentoring tailored to biodata and initial observations. Training and intervention through mentoring provided capacity building for the Fishermen group in District Maladum Mes based on 79% post test results and training output achieved in the form of all partners having e-mail accounts, social media accounts, and video conference accounts.